New Horizons In Education: Positive Education And Emerging Leadership Roles Of Counselors - Bozkurt, Aysun Tülay (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2013)
Positive Psychology is a movement, which has grown so rapidly in the last decade driven by a concern for the systematic study of positive aspects of human development rather than mental disease. Happiness, positive traits, positive emotions and positive institutions are the prevalent research topics studied under the name of positive psychology with empirical validations about their positive effects on self enhancement and prevention from mental illness. Positive Psychology has quite extensive fields of application in business administration, law (forensic psychology), clinical psychology, counseling, health and education all concern about institutional and individual mechanisms that set the positive potentials of individuals into practice in order to be at their best. This article reviews conceptual foundations of positive psychology and how its principles are integrated in education holistically. The article proposes a system model where meso and micro level indicators of positive psychology/education interacts within an eco system where the role of school counselors as change agents becomes crucial. Mindsets and other potential barriers for the counselors are discussed along with resolution strategies. (C) 2014 Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/3.0/).
Keywords: positive psychology; positive education; strength based counseling